Morphological and acoustic identification of Hipposiderids (Chiroptera: Hipposideridae) from Xuan Son national park, Northeastern Vietnam - Thong, Vu Dinh (Academia Journal of Biology, 2016)
Xuan Son National Park is a well known locality in Vietnam for its karst landscape and biodiversity values. The park contains a large number of caves, which are homes to 20 bat species belonging to 13 genera, four families. Of which, four species, viz. Aselliscus stoliczkanus, Hipposideros armiger, H. larvatus and H. pomona, belong to the family Hipposideridae. Prior to 2010, almost all bat researchs at the park focused on taxonomy. Between 2011 and 2015, the author conducted a series of field surveys with emphases on both taxonomy and echolocation of hipposiderids. External measurements of every captured bat were taken for taxonomic assessments. Echolocation calls were recorded from natural habitats while bats flying and different situations inside a flight-tent. Results from the surveys indicated that, within Xuan Son National Park, each hipposiderid species is clearly distinguishable from the remainders of the family Hipposideridae in both morphology and echolocation frequency. This paper provides acoustic and morphological diagnoses of hipposiderids for practical monitoring, further studies and conservation of hipposiderids at the park in the future.